2019
DOI: 10.3389/fneur.2019.01166
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Dosimetry of Computed Tomography- and Fluoroscopy-Guided Intrathecal Therapy With Nusinersen in Adult Patients With Spinal Muscular Atrophy

Abstract: Background: Spinal muscular atrophy (SMA) is a genetic disorder that leads to progressive tetraparesis. Nusinersen is the first approved drug for the treatment of SMA and is administered via intrathecal injections. Neuromyopathic scoliosis and spondylodesis can impede lumbar punctures, thus necessitating the use of radiological imaging. Furthermore, dosimetry of this potentially lifelong therapy should be supervised.Methods: Fluoroscopy-assisted or computed tomography (CT)-guided intrathecal injections of nusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 46 publications
0
26
1
1
Order By: Relevance
“…Previous studies have specifically examined radiation exposure during nusinersen injection using fluoroscopy and CT guidance and have found similar results to our estimation. Repeated radiation exposure for the delivery of nusinersen is a risk that needs to be balanced with the benefit of the treatment, and further research into this topic is needed 2–4 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have specifically examined radiation exposure during nusinersen injection using fluoroscopy and CT guidance and have found similar results to our estimation. Repeated radiation exposure for the delivery of nusinersen is a risk that needs to be balanced with the benefit of the treatment, and further research into this topic is needed 2–4 …”
Section: Discussionmentioning
confidence: 99%
“…Five randomized placebo controlled clinical trials and three open label trials evaluated medications (valproic acid, gabapentin, salbutamol, hydroxyurea and nusinersen) in adults with SMA type II and III (n = 362 participants, follow up 6-12 months), using different measures of muscle strength and function: four showed no statistically significant effects on the outcome measures, and an open label study of nusinersen showed mean improvement of 8.25 m in the 6 min walk test (p = 0.01), Taken together these were rated as providing Level 1-4 evidence (Table 2) on the Oxford Centre for Evidencebased Medicine scale. Seven case series reported administration of intrathecal nusinersen, with radiological guidance an option for administration, using transforaminal or interlaminar approaches +/− laminotomy [89][90][91][92][93][94][95]. Lumbar punctures were mostly well tolerated, adverse events included post lumbar headache and subarachnoid haemorrhage.…”
Section: Medicationsmentioning
confidence: 99%
“…The technical procedure of CT-guided LP for intrathecal nusinersen administration is well described in the literature; however, details on the radiation exposure are often excluded 6 . Recent studies showed that radiation exposure during nusinersen administration in SMA patients is generally not higher compared to those for patients with normal spine anatomy 6,15 . Interestingly, a decrease of the radiation dose during therapy with nusinersen has been demonstrated, probably due to decreased frequency of imaging, data from successful previous injections, and a learning effect of the interventionalists 3,7,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that radiation exposure during nusinersen administration in SMA patients is generally not higher compared to those for patients with normal spine anatomy 6,15 . Interestingly, a decrease of the radiation dose during therapy with nusinersen has been demonstrated, probably due to decreased frequency of imaging, data from successful previous injections, and a learning effect of the interventionalists 3,7,15 . Direct comparisons of radiation dosage or patient exposure between the studies is limited because different units (mSv vs. mGy•cm 15 ) and different statistical values (median vs. mean 2 ) were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation